DEPDC1B Promotes Melanoma Angiogenesis and Metastasis through Sequestration of Ubiquitin Ligase CDC16 to Stabilize Secreted SCUBE3. Issue 10 (27th January 2022) - Hu, Feng; Fong, Ki On; Cheung, May Pui Lai; Liu, Jessica Aijia; Liang, Rui; Li, Tsz Wai; Sharma, Rakesh; IP, Philip Pun‐Ching; Yang, Xintao; Cheung, Martin
Abstract: The ability of melanoma to acquire metastasis through the induction of angiogenesis is one of the major causes of skin cancer death. Here, it is found that high transcript levels of DEP domain containing 1B ( DEPDC1B ) in cutaneous melanomas are significantly associated with a poor prognosis. Tissue microarray analysis indicates that DEPDC1B expression is positively correlated with SOX10 in the different stages of melanoma. Consistently, DEPDC1B is both required and sufficient for melanoma growth, metastasis, angiogenesis, and functions as a direct downstream target of SOX10 to partly mediate its oncogenic activity. In contrast to other tumor types, the DEPDC1B‐mediated enhancement of melanoma metastatic potential is not dependent on the activities of RHO GTPase signaling and canonical Wnt signaling, but is acquired through secretion of signal peptide, CUB domain and EGF like domain containing 3 (SCUBE3), which is crucial for promoting angiogenesis in vitro and in vivo. Mechanistically, DEPDC1B regulates SCUBE3 protein stability through the competitive association with ubiquitin ligase cell division cycle 16 (CDC16) to prevent SCUBE3 from undergoing degradation via the ubiquitin‐proteasome pathway. Importantly, expression of SOX10, DEPDC1B, and SCUBE3 are positively correlated with microvessel density in the advanced stage of melanomas. In conclusion, it is revealed that a SOX10‐DEPDC1B‐SCUBE3 regulatory axis promotes melanoma angiogenesis and metastasis, which suggests that targeting secreted SCUBE3 can be a therapeutic strategy against metastatic melanoma. Abstract : An oncogenic mechanism is unraveled by which DEPDC1B functions downstream of SOX10 to promote melanoma angiogenesis and metastasis. DEPDC1B competitively interacts with CDC16 in the cytosol to block the ubiquitination and degradation of SCUBE3, enabling stabilized SCUBE3 to be secreted from melanoma cells for blood vessel recruitment to facilitate their growth, survival, and metastasis.